2019
DOI: 10.1101/791079
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

OncogenicGata1causes stage-specific megakaryocyte differentiation delay

Abstract: Scientific Category: Haematopoiesis and Stem Cells Key PointsGATA1s-induced stage-specific differentiation delay increases immature megakaryocytes in vivo and in vitro, during development.Differentiation delay is associated with increased numbers of cells in S-phase and reduced apoptosis. AbstractThe megakaryocyte/erythroid Transient Myeloproliferative Disorder (TMD) in newborns with Down Syndrome (DS) occurs when N-terminal truncating mutations of the hemopoietic transcription factor GATA1, that produce GATA1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In this study, we did not observe a significant increase in the number and proliferation of MK progenitors nor on the output of MKs defined as CD41 + CD42 + cells upon engineering of GATA1s. This is consistent with the effect of Gata1s on murine ES cells ( 13 ) and the recent observation showing that the increased MK output generated by GATA1s is due to a shift in HSC differentiation toward the MK lineage rather than to a direct effect on MK progenitors ( 18 , 19 ). However, our results showed a marked synergy between SMC3 +/– and GATA1s on both proliferation (e.g., increased MK progenitor number and size of MK colonies) and ploidization.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we did not observe a significant increase in the number and proliferation of MK progenitors nor on the output of MKs defined as CD41 + CD42 + cells upon engineering of GATA1s. This is consistent with the effect of Gata1s on murine ES cells ( 13 ) and the recent observation showing that the increased MK output generated by GATA1s is due to a shift in HSC differentiation toward the MK lineage rather than to a direct effect on MK progenitors ( 18 , 19 ). However, our results showed a marked synergy between SMC3 +/– and GATA1s on both proliferation (e.g., increased MK progenitor number and size of MK colonies) and ploidization.…”
Section: Discussionsupporting
confidence: 92%
“…How GATA1s and these secondary mutations cooperate to induce AMKL and why this leukemia development requires a T21 and a fetal hematopoiesis remain unclear and need modeling approaches. Mouse models have been limited by only minor defects induced by Gata1s in late megakaryocyte (MK) differentiation ( 10 13 ). Thus, it was crucial to develop human models of DS-AMKL.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, GATA1 has been reported to have antiapoptotic functions (Aguirre et al 2010 ; Juban et al 2021 ). In current manuscript, we did not find statistical difference of erythroblast apoptosis between wild-type and knockout mice in the bone marrow and spleen (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…GATA1s promotes megakaryocytic progenitor expansion and disrupts megakaryocytic and erythroid differentiation ( Shimizu et al, 2009 ; Chlon et al, 2015 ; Banno et al, 2016 ; Juban et al, 2021 ). This appears to involve synergistic interactions with other leukemogenic molecules; for example, GATA1s increases expression of miRNA-486-5p, an erythroid oncogenic miRNA ( Shaham et al, 2015 ).…”
Section: Gata1 Mutationsmentioning
confidence: 99%
“…Evidence from a range of cellular and animal disease models confirmed that TAM is initiated by increased gene dosage from chromosome 21 acting in cooperation with GATA1s . GATA1s mutation alone disrupts differentiation of megakaryocytes and promotes expansion of myeloid and megakaryocytic progenitors, while production of aberrant megakaryoblasts is strengthened on the background of trisomy 21 ( Banno et al, 2016 ; Juban et al, 2021 ; Matsuo et al, 2021 ). TAM requires the synergy between trisomy 21 and GATA1s but leukemic transformation may be independent of trisomy 21 ( Wagenblast et al, 2021 ; Arkoun et al, 2022 ).…”
Section: Gata1 Mutationsmentioning
confidence: 99%